2013
DOI: 10.1007/s11739-013-0945-7
|View full text |Cite
|
Sign up to set email alerts
|

COPD patients with and without metabolic syndrome: clinical and functional differences

Abstract: Chronic obstructive pulmonary disease (COPD) and the metabolic syndrome (MetS) are considered public health challenges of the 21st century. The coexistence of MetS in COPD patients and any clinical differences between COPD patients with and without MetS have not been extensively studied. We aimed to describe the clinical characteristics of patients with MetS and COPD. An observational, multicenter study of 375 patients hospitalized for a COPD exacerbation with spirometric confirmation was performed. We measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
55
1
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 27 publications
12
55
1
7
Order By: Relevance
“…The later was also shown by many studies reporting the highest MetS prevalence in patients with GOLD stage II compared to higher GOLD stages (28,29,32,34,36). This observation could be due to a relatively higher influence of lifestyle on body composition and metabolic health in less advanced disease compared to COPD induced triggers on the wasting process in advanced disease (45).…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…The later was also shown by many studies reporting the highest MetS prevalence in patients with GOLD stage II compared to higher GOLD stages (28,29,32,34,36). This observation could be due to a relatively higher influence of lifestyle on body composition and metabolic health in less advanced disease compared to COPD induced triggers on the wasting process in advanced disease (45).…”
Section: Discussionmentioning
confidence: 67%
“…These studies showed more inhaled or oral steroid use, more statin use, more beta-blockers use and more antihypertensives in the MetS group compared to the non-MetS group. No differences were found in use of anti-diabetics, insulin and long term oxygen therapy (28,30).…”
Section: Contributing Factors Of Mets In Copdmentioning
confidence: 91%
See 3 more Smart Citations